Studies on exhaust gas recycling and waste heat recovery for the Z12V190 diesel engine - XUEJUN, HOU; NASR-EI-DIN, H.A.; QIMIN, LIANG; LONGZHU, GAO (Kuwait Journal of Science, 2015)
The Z12V190 diesel engine has high fuel consumption and low thermal efficiency, and releaseslarge amounts of diesel exhaust gas and waste heat into the atmosphere. This causes hugeresource as well as energy waste. In order to protect the environment, save energy, and alsoto solve these problems about exhaust gas recycling and waste heat recovery, the Z12V190diesel engine exhaust emission rate and minimum gas injection rate for gas underbalanceddrilling are calculated and compared with the deduced formulas. The critical point pressurerange of different diameter drill pipe has been deduced in the same diameter well, whichproved the application feasibility of the Z12V190 diesel engine exhaust gas underbalanceddrilling. Meanwhile, the waste heat recovery rate has been calculated and proved the economicfeasibility of the Z12V190 diesel engine exhaust gas waste heat recovery. The process flows aredesigned for the Z12V190 diesel engine exhaust gas underbalanced drilling well and its wasteheat recovery. The Z12V190 diesel engine exhaust gas will be recycled to reduce pollution, andits waste heat recovery be used for saving energy resources.